Avant : a fintech's revolution with banks - Markovich, Sarit; Mahoney, Jack (London : Kellogg School of Management, 2019)
Suk Shah, the chief financial officer at Avant, needs to consider the marketplace lender's future relationship with traditional banks: Might Avant and the banks be able to work together as complementors to offer loans to consumers, or must they always be competitors? The case describes Avant's operation, highlighting the advantages and disadvantages that marketplace lenders and, more generally, fintechs have relative to traditional financial institutions. Shah's decision must take into account the challenges marketplace lenders face in terms of customer acquisition costs and in attracting investors to its platform. Avant faces competition from other marketplace lenders, like LendingClub, as well as competition from banks. Regulation also has an important effect on Avant's ability to directly compete with banks and its need to cooperate with them.
Originally Published In Markovich, S., & Mahoney, J. (2019). Avant: A Fintech's (R)evolution with Banks. 5-318-505. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Finance companies -- Case studies; Banks and banking -- Case studies; Peer-to-peer loans -- Case studies